Особливості клітинної ланки імунної системи у щурів з гострим гепатитом на тлі мерказоліл-індукованого гіпотиреозу = Cellular features of the immune system of rats with acute hepatitis combined with merkazolil-induced hypothyroidism - O. Y. Zarichna; I. M. Klishch; I. Ya. Krynytska (Kazimierz Wielki University, 2015)
Zarichna O. Y., Klishch I. M., Krynytska I. Ya. Особливості клітинної ланки імунної системи у щурів з гострим гепатитом на тлі мерказоліл-індукованого гіпотиреозу = Cellular features of the immune system of rats with acute hepatitis combined with merkazolil-induced hypothyroidism. Journal of Education, Health and Sport. 2015;5(8):85-90. ISSN 2391-8306. DOI 10.5281/zenodo.27248 http://dx.doi.org/10.5281/zenodo.27248 https://pbn.nauka.gov.pl/works/604305 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-fa2ae17c-9ef3-4fcb-bf3f-8baf66fb89c5 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A85-90 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 25.07.2015.   УДК [612.017.1-02:616.36-002.1-06:616.441-008.64]-092.9   ОСОБЛИВОСТІ КЛІТИННОЇ ЛАНКИ ІМУННОЇ СИСТЕМИ У ЩУРІВ З ГОСТРИМ ГЕПАТИТОМ НА ТЛІ МЕРКАЗОЛІЛ-ІНДУКОВАНОГО ГІПОТИРЕОЗУ CELLULAR FEATURES OF THE IMMUNE SYSTEM OF RATS WITH ACUTE HEPATITIS COMBINED WITH MERKAZOLIL-INDUCED HYPOTHYROIDISM   O. Y. Zarichna, I. M. Klishch, I. Ya. Krynytska Зарічна О. Й., Кліщ І. М., Криницька І. Я.   ДВНЗ «Тернопільський державний медичний університет імені І. Я. Горбачевського МОЗ України» SHEI "Ternopil State Medical University by I. Ya Horbachevsky of MPH of Ukraine"   Резюме. В експерименті на щурах з модельованим гіпотиреозом, гострим галактозаміновим гепатитом та гострим гепатитом на тлі гіпотиреозу  проведено дослідження змін показників клітинного імунітету в крові. Результати проведеного дослідження вказують на виражені порушення з боку клітинної ланки імунітету крові у вигляді Т-лімфоцитопенії, дисбалансу субпопуляційного складу Т-лімфоцитів з переважним зменшенням Т-хелперів, зменшення імунорегуляторного індексу та  зниження вмісту загальних В-лімфоцитів у тварин з гіпотиреозом. Т-лімфоцитоз, дисбаланс субпопуляційного складу Т-лімфоцитів з переважним підвищенням Т-хелперів, збільшення імунорегуляторного індексу та  підвищення вмісту загальних В-лімфоцитів встановлено у тварин з гострим гепатитом. Найсуттєвішого пригнічення клітинної ланки імунітету зазнали щурі з гострим гепатитом на тлі гіпотиреозу.   Ключові слова: гострий гепатит, гіпотиреоз, клітинний імунітет.   SUMMARY. In experiments on rats with modulated hypothyroidism, acute  galactosamine hepatitis, acute hepatitis combined with merkazolil- induced hypothyroidism the changes in the indexes of cellular immunity in blood were studied. Results of the investigation indicate a pronounced imbalance of blood cellular immunity in the form of T-lymphocytopenia, imbalance subpopulation of T-lymphocytes with a predominant decreasing in T-helper cells, reducing the immunoregulatory index and decreasing of total B-lymphocytes in rats with hypothyroidism. T-lymphocytosis, imbalance subpopulation of T-lymphocytes with a predominant increasing in T-helper cells, increasing of immunoregulatory index and increasing of B-lymphocytes was determined in rats with acute hepatitis. Rats with acute hepatitis combined with merkazolil- induced hypothyroidism had the most significant suppression of cellular immunity.   Key words: acute hepatitis, hypothyroidism, cellular immunity.